Determinants of Teacher Motivation and Performance: Individual Characteristics, Job, and Organizational Climate - Nasar, Ismail; Sarwan; Rahmi, Wifqi; Istifadah; Aziz, Mohd Kasturi Nor Abd; Partono (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to (1) describe individual characteristics, job characteristics, organizational climate, work motivation, and teacher performance, (2) analyze the influence of individual characteristics, job characteristics, and organizational climate on work motivation, (3) test their influence on teacher performance, (4) examine the influence of work motivation on teacher performance, and (5) explore the mediating role of work motivation in the relationship between individual characteristics, job characteristics, organizational climate, and teacher performance. This explanatory study involved teachers from SMA Maarif NU in Pasuruan in 20 districts, with a population of 485 teachers. The proportional random sampling method was used to select 110 teachers. Data were collected using a structured instrument distributed to respondents. The results showed that: (1) individual characteristics are shaped by interests, attitudes, and needs; job characteristics by skill diversity, task identity, task clarity, autonomy, and feedback; organizational climate by responsibility, identity, warmth, support, and conflict; work motivation by achievement, recognition, work rewards, and personal development; and teacher performance by professional, personal, and social competence. (2) Individual characteristics, job characteristics, and organizational climate have a positive effect on work motivation. (3) These variables also have a positive impact on teacher performance. (4) Work motivation significantly improves teacher performance. (5) Work motivation mediates the influence of individual characteristics, job characteristics, and organizational climate on teacher performance. This study concludes that work motivation plays an important role as an intervention, with the total influence of these variables on performance exceeding the direct influence